The New Mexico state constitution - Smith, Chuck, 1941- (Oxford commentaries on the state constitutions of the United States., 2011)
'The New Mexico State Constitution' provides an outstanding constitutional and historical account of the state's governing charter. It begins with an overview of New Mexico's constitutional history, and then provides an in-depth, section-by-section analysis of the entire constitution, detailing important changes that have been made since its drafting.